The effect of gratitude intervention on anxiety and depressive symptoms among university students in Malaysia - Kamarulzaman, Nur Syahrain (2021)
Gratitude is related to lesser depression and anxiety level. In this study, we tested the effectiveness of a newly developed gratitude intervention protocol which combines several gratitude-based activities that have been thoroughly studied in previous research with some modifications on the available activities. The aim of this study was to measure the effect of the four-week gratitude intervention program on anxiety and depressive symptoms, positive affect, negative affect, and gratitude. Participants (N = 43) were recruited among undergraduate students of one public university in Malaysia. A total of 22 participants were assigned to the gratitude intervention group, and another 21 participants were assigned to the control group. Instruments used to measure the outcome variables include the 21-item Malay translated Depression Anxiety Stress Scale (Malay-DASS), Positive and Negative Affect Schedule (PANAS), and the six-item Gratitude Questionnaire (GQ-6). The stated questionnaires were given as pre-assessment and post-assessment after completion of the 4-week intervention program. The results of the study show that the gratitude intervention program led to a significant reduction in depressive and anxiety symptoms, lower negative affect, as well as increase in positive affect and gratitude level. These findings suggest that gratitude intervention may be helpful to improve the psychological state of university students in Malaysia. These findings are in agreement with the broaden-and-built theory which suggest that gratitude as a positive emotion helps to broaden people’ way of thinking instead of just focusing on the negatives which also encourage people to explore resources available that will help them to build more positive experiences. These skills developed from the experience of gratitude are important to help people cope with emotional difficulties and life adversities, which explain why the gratitude intervention caused reduction in depressive and anxiety symptoms.